Чому точність вимірювання фізичних величин обмежена - Gorban, I. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The research results explaining the restriction causes of measurement precision of real physical variables are presented. It is shown that the imperfect character of the phenomenon of statistical stability that manifests itself in misconvergence (inconsistency) of statistical estimates is a key element in the precision limitation. The peculiarities of the law of average and the central limit theorem of probability theory under conditions of violation of statistical stability are determined. The results of theoretical research are confirmed by experiments. It is drawn to attention that real estimates have hyper-random character. Their hyper-random nature becomes evident when the sample size is large.